The Impact Of The Smart Economy On Smart Living With The Mediator Of The National Economy In Indonesia - Lubis, Nadia Octaviana; Astuti, Yuhana (UNIVERSITAS PAKUAN, 2024)
The national economy includes increasing output and productivity, government spending policies, infrastructure development initiatives, and cooperation with other countries. In Indonesia, economic growth and technological advances result from the government and community collaboration in building smart cities. A critical dimension of a Smart City is a Smart Economy and Smart Living, which aim to improve city performance, create innovation, encourage e-commerce, and ensure the feasibility of people's living standards. This study aims to examine the impact of the Smart Economy on Smart Living in Indonesia, with a particular focus on the mediating role of national economic performance. The methodology used is quantitative, with statistical analysis of Partial Least Square Structural Equation Modeling (PLS-SEM) using the Smart PLS 4 application. The population of this study includes smart cities in Indonesia, and purposive sampling techniques were applied to select relevant samples. This research examines the main dimensions of a Smart City, namely Smart Economy and Smart Living, and their related indicators. The study results show that the Smart Economy positively and significantly influences Smart Living in Indonesia. Moreover, national economic performance also plays a positive and significant mediating role in this relationship. However, the variance accounted for (VAF) test shows that only 16% of the total effects of Smart Economy on Smart Living are mediated by national economic performance, indicating that while this mediation relationship is statistically significant, the mediation effect is weak. This research provides insight into the relationship between economic performance and quality of life in the context of smart-city initiatives